A Real-Effort Experiment on Gift Exchange with Temptation - Alexander K. Koch; Julia Nafziger (Institute for the Study of Labor (IZA), 2015)
We conduct a real-effort experiment to test whether workers reciprocate generous wages by managers when workers are tempted to surf the internet. Further, we investigate how an active policy of restricting the usage of the internet affects the workers' motivation. We observe that the temptation of the internet hampers workers' willingness to reciprocate fair wages. Yet, when the manager makes an active choice not to deny internet access, workers perceive the "freedom from control" as a gift which they reciprocate with high effort. Whether the positive "freedom from control" aspect or the negative temptation aspect dominates depends on the worker's reciprocity: for highly reciprocal workers the control aspect dominates; for non-reciprocal workers the temptation aspect dominates.
Keywords: C91; D03; J33; M52; 330; gift exchange; temptation; hidden costs of control